Enhancing farmer's participation in plant breeding: Community Biodiversity Development and Conservation Program (CBDC), Bohol project, Philippines - Ramos, Hidelisa M. de (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
The Community Biodiversity Development and Conservation Program (CBDC) is a global undertaking aimed at halting or minimizing genetic erosion and strengthening the farmers' role in on-farm conservation and development of plant genetic resources (PGR). It also aims to seek ways on how the formal and informal sectors can complement each other in on-form conservation and developmental. In this paper, the project's general approach is illustrated in a case study on rice, conducted in Bohol, Philippines. The objectives of Ihe study were to increase the genetic diversity of rice planted by farmers and to determine farmers' criteria for evaluating and selecting rice. Genetic materials were distributed to farmer-partners, evaluated by farmers, and subsequently exchanged within Ihe community through the local exchange system. Workshops were conducted every season to identify researchable areas and to design field experiments. Community workshops were also held lo analyze research results and identify new problems for the next season. Farmers decided which varieties or technology to adopt after each season, based on their observations and evaluation of the on-farm research. The study documented the results of two types of farmers' evaluation of the varieties.